2018
DOI: 10.1002/slct.201802876
|View full text |Cite
|
Sign up to set email alerts
|

An Economical Synthesis of Caulerpin and Evaluation of Its New Anticancer Activities

Abstract: Caulerpin was economically synthesized with a new easy‐handled procedure in higher overall yield of 25.4%, compared to overall yield of 11% in reported literature. Evaluation of caulerpin in new types of cancer cell lines was performed and generally excellent biological activities were observed. In which, caulerpin showed the most activity in human liver tumor cell line (Huh7: IC50 =0.7 μM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In Li's experiment, when Knoevenagel condensation between 1 a is about to proceed, formaldehyde group at C−3 position will always be activated by piperidine first, forming a nitrogenous base – substrates binding intermediate which is more susceptible to electron's attack. The special intermediate with m/z 285 (positive mode) was found in reaction system when it were refluxed 5 min [5c] . On the basis of this record, we considered two classic mechanism of KC reaction as we known, put tryptophan as the nitrogenous base into mechanism graph and inferred some intermediates‘ m/z peak signal.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In Li's experiment, when Knoevenagel condensation between 1 a is about to proceed, formaldehyde group at C−3 position will always be activated by piperidine first, forming a nitrogenous base – substrates binding intermediate which is more susceptible to electron's attack. The special intermediate with m/z 285 (positive mode) was found in reaction system when it were refluxed 5 min [5c] . On the basis of this record, we considered two classic mechanism of KC reaction as we known, put tryptophan as the nitrogenous base into mechanism graph and inferred some intermediates‘ m/z peak signal.…”
Section: Resultsmentioning
confidence: 98%
“…We used the most up to date method to synthesise the intermediate methyl 2‐(3‐formyl‐1H‐indol‐2‐yl)acetate) by following two substitution reactions from indole [5c] . Thereafter the intermediates were dimerized by the intermolecular Knoevenagel reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the cytotoxic activity of the extract of C. cylindracea , and two isolates caulerpin and monomethyl caulerpinate were also investigated against the aggressive breast cancer cell line MDA-MB-231 for the first time besides breast cell line MCF-7. In fact, in a previous studies, caulerpin was evaluated by Li et al against a panel of human cancer cell lines, and IC 50 values were found to be 4.67 (human leukemia: K562), 4.20 (human lung: A549), 1.95 (human cervical: HeLa), 4.04 (human colon: HT29), 3.71 (human breast: SK-BR-3), and 0.72 (human liver: Huh7) μM, 39 but not on MDA-MB-231 and MCF-7 breast cell lines.…”
Section: Introductionmentioning
confidence: 99%